2018
DOI: 10.1155/2018/8917535
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Strategies and Physical Activity in Older Adults: A Discriminant Analysis

Abstract: Background Although a number of studies have examined sociodemographic, psychosocial, and environmental determinants of the level of physical activity (PA) for older people, little attention has been paid to the predictive power of cognitive strategies for independently living older adults. However, cognitive strategies have recently been considered to be critical in the management of day-to-day living. Methods Data were collected from 243 men and women aged 55 years and older living in France using face-to-fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 60 publications
1
6
0
1
Order By: Relevance
“…The level of accuracy recorded for classification model in the present study is high, compared to some of the published levels for discriminant analysis to categorise older adults based on different criterion features. Recently a study reported accuracy of 73% for five predictor variables including cognitive function to identify individuals at high risk of lapses once engaged in regular physical activity [ 35 ]. A similar lower accuracy of 78.2% was reported using five predictor variables for detecting individuals at high risk of depression among community-dwelling older adults [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The level of accuracy recorded for classification model in the present study is high, compared to some of the published levels for discriminant analysis to categorise older adults based on different criterion features. Recently a study reported accuracy of 73% for five predictor variables including cognitive function to identify individuals at high risk of lapses once engaged in regular physical activity [ 35 ]. A similar lower accuracy of 78.2% was reported using five predictor variables for detecting individuals at high risk of depression among community-dwelling older adults [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Barriers provide information about the potential constraints on action as perceived by individuals. Generally, this kind of barrier is reported more specifically by vulnerable persons, such as cancer survivors, for whom experienced nausea, fatigue, a lack of time and a lack of external support contribute to directly hindering exercise as a routine [ 79 , 80 , 81 , 82 ]. This distinction is not obvious in studies, and authors have to appropriately formulate perceived barriers when using the TTM as a theoretical framework.…”
Section: Discussionmentioning
confidence: 99%
“…Practicing exercise regularly also requires planning the exercise sessions in the coming week (i.e., goal setting), remembering when to exercise at the planned time (i.e., prospective memory), and accepting that positive effects of PA occur in the long term (i.e., delay of gratification), which are three higher cognitive functions directly related to EF 9, 40, 41. The predictive power of EF on PA engagement has been mainly demonstrated with cross-sectional studies 42, 43. To our knowledge, no intervention study has been conducted with the aim of demonstrating a causal link between an improvement in EF efficiency and adherence to exercise.…”
Section: Causal Relationship Between Efs and Effortful Control And Admentioning
confidence: 99%